Assessing the Effectiveness of P5 on the Theme of Local Wisdom: A Countenance Stake Model Evaluation - Novitas, Ahmila; Dwikurnaningsih, Yari (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to evaluate the achievement of criteria in the implementation of Strengthening Pancasila Student Profile Project (P5) with the theme of Local Wisdom. This study used an evaluation research method applying the Countenance Stake evaluation model, which consists of three stages: Antecedent, Transaction, and Outcomes. The study employed both qualitative and quantitative data collection techniques, with data collected through observation, interviews, document studies, and questionnaires involving 66 respondents. Data analysis utilized descriptive quantitative analysis (percentage scores of achievement for each school in every stage) and qualitative analysis (descriptions of strengths, challenges, and influencing factors). The evaluation of the P5 program based on the Countenance model shows positive results across the three stages. In the Antecedents stage, schools demonstrated high readiness, with average achievements ranging from 85.1% to 86.3%. The Transactions stage showed satisfactory implementation, with achievements between 76.9% and 85.2%. In the Outcomes stage, student performance was fairly good, ranging from 75.2% to 81.5%. The study highlights the importance of management support, teacher training, and robust monitoring and evaluation systems for effective program implementation. Strengthening these aspects is crucial for ensuring the P5 program runs more effectively and equitably across all schools.